Ursolic acid inhibits the development of nonalcoholic fatty liver disease by attenuating endoplasmic reticulum stress1. Issue 5 (13th May 2015) - Li, Jian-Shuang; Wang, Wen-Jun; Sun, Yu; Zhang, Yu-Hao; Zheng, Ling
<x xml:space="preserve">Abstract</x> Ursolic acid treatment inhibits steatosis by reducing hepatic ER stress.